2014
DOI: 10.1021/ie404441a
|View full text |Cite
|
Sign up to set email alerts
|

Selective Transformation of 5-Hydroxymethylfurfural into the Liquid Fuel 2,5-Dimethylfuran over Carbon-Supported Ruthenium

Abstract: A simple and efficient process was presented for the selective hydrogenation of 5-hydroxymethylfurfural (HMF) into the high-quality liquid fuel 2,5-dimethylfuran (DMF) in the presence of tetrahydrofuran (THF). Among the employed metal catalysts, the relatively inexpensive carbon-supported ruthenium (Ru/C) displayed the highest catalytic performance, which led to 94.7% DMF yield with 100% HMF conversion at a relatively mild reaction temperature of 200 °C for only 2 h. Although Ru/ C had a little loss in the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
126
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 35 publications
5
126
0
2
Order By: Relevance
“…[15] Vlachos and co-workers reported the catalytic transfer hydrogenation (CTH) of HMFt oD MF by using secondary alcohols as the H-donors over aR u/C catalyst with aD MF yield of up to 80 %, [16] and then the role of Ru and RuO 2 phases was studied in detail. [20] Kawanami and co-workersr eportedt he use of supercritical CO 2 -watero nt he HDO of HMF over aP d/C catalyst, and av ery high yield (100 %) of DMF was observed at 80 8Ca fter 2h. [18] Wang and co-workersr eported the HDO of HMF over Ru/ Co 3 O 4 at 130 8Ca nd 0.7 MPa H 2 in THF with aD MF yield of 93.4 %.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Vlachos and co-workers reported the catalytic transfer hydrogenation (CTH) of HMFt oD MF by using secondary alcohols as the H-donors over aR u/C catalyst with aD MF yield of up to 80 %, [16] and then the role of Ru and RuO 2 phases was studied in detail. [20] Kawanami and co-workersr eportedt he use of supercritical CO 2 -watero nt he HDO of HMF over aP d/C catalyst, and av ery high yield (100 %) of DMF was observed at 80 8Ca fter 2h. [18] Wang and co-workersr eported the HDO of HMF over Ru/ Co 3 O 4 at 130 8Ca nd 0.7 MPa H 2 in THF with aD MF yield of 93.4 %.…”
Section: Introductionmentioning
confidence: 99%
“…For example, HMF is derived from glucoseand can be converted into various fuel molecules and valuable industrialchemicals. [5][6][7][8][9][10][11][12][13][14][15] For example, 81 %D MF yield was achieved at full HMF conversion using Ru/C in isopropanol solutions. [4] The production of DMF from HMF hydrogenolysis in organic solvents was studied by means of catalytic transfer hydrogenation and also using molecular hydrogen, achieving high selectivity and yield.…”
mentioning
confidence: 99%
“…These studies demonstrated different yields and conversion rates. The highest 2,5-DMF yield was reported by Hu et al [70], which reached 94.7% with total HMF conversion at a reaction temperature of 473 K for 2 h. The results showed that further temperature increase up to 533 K did not affect 2,5-DMF yields [45].…”
Section: Furan and Substituted Furansmentioning
confidence: 71%
“…The use of Ru/C catalysts for the hydrogenation of HMF to 2,5-DMF was extensively investigated in a number of studies [36,45,[67][68][69][70] under various temperature ranges and using difference hydrogen sources. These studies demonstrated different yields and conversion rates.…”
Section: Furan and Substituted Furansmentioning
confidence: 99%